Product innovation and adoption in market equilibrium: the case of digital cameras (2007)
This paper contains an empirical dynamic model of supply and demand in the mar- ket for digital cameras with endogenous product innovation. On the demand side, het- erogeneous consumers time optimally the purchase of goods depending on the expected evolution of prices and characteristics of available cameras. On the supply side, firms introduce new camera models accounting for the dynamic value of new products and the optimal behavior of consumers. The model is estimated using data from the market for digital cameras and the estimated model replicates rich dynamic features of the data. The estimated model is used to perform counterfactual computations, which suggest that more competition or lower product introduction costs generate more product variety but lower average product quality